In Vivo Quantification Reveals Extensive Natural Variation in Mitochondrial Form and Function in Caenorhabditis briggsae - Hicks, Kiley A. (Public Library of Science, 2012)

(untitled)
We have analyzed natural variation in mitochondrial form and function among a set of Caenorhabditis briggsae isolates known to harbor mitochondrial DNA structural variation in the form of a heteroplasmic nad5 gene deletion (nad5Δ) that correlates negatively with organismal fitness. We performed in vivo quantification of 24 mitochondrial phenotypes including reactive oxygen species level, membrane potential, and aspects of organelle morphology, and observed significant among-isolate variation in 18 traits. Although several mitochondrial phenotypes were non-linearly associated with nad5Δ levels, most of the among-isolate phenotypic variation could be accounted for by phylogeographic clade membership. In particular, isolate-specific mitochondrial membrane potential was an excellent predictor of clade membership. We interpret this result in light of recent evidence for local adaptation to temperature in C. briggsae. Analysis of mitochondrial-nuclear hybrid strains provided support for both mtDNA and nuclear genetic variation as drivers of natural mitochondrial phenotype variation. This study demonstrates that multicellular eukaryotic species are capable of extensive natural variation in organellar phenotypes and highlights the potential of integrating evolutionary and cell biology perspectives.